LAND REFORM IN SOUTH AFRICA: OBSTINATE SPACIAL DISTORTIONS - Maake, Manala Shadrack (Africanus: Journal of Development Studies, 2016)
This theoretical paper seeks to make a significant contribution to the South African land reform discourses. The paper argues that the pace of land redistribution in South Africa is static, and therefore limits the livelihood choices of most intended beneficiaries of the land reform programme. The primacy of the programme within rural development ought to be measured and assessed through ways in which the land reform programmes conform to and improve the livelihoods, ambitions and goals of its intended beneficiaries without compromising agricultural production and the economy. Additionally, this paper highlights the slow pace of the land reform programme and its implications for the socio-economic transformation of South Africa. The paper concludes by demonstrating the need for a radical approach towards land reform which will not disrupt agricultural production, and further secure support and coordination of spheres of government. The democratic government in South Africa inherited a country which is characterised by extreme racial imbalances associated with social relations to land and overt spatial distortions. Non-white South Africans are spatially plagued with feeling the effects of colonial and apartheid legal enactments which sought to segregate ownership of resources on the basis of race. Consequently, the democratic government is mandated to formulate land reform measures to aid the reversal of colonially fuelled spatial distortions. Thus, coordination between the spheres of government, markets forces and civil society is indispensable in the accomplishment of satisfactory land reform.